Analysis and characterization of Fátima Watershed Located in the city of Frederico Westphalen-RS - Haas, Aline; Conceição, Sabrina Rodrigues da; Henrichsen, Jessica Luana; Chinazzo, Igor Brendler; Ritter, Luciana Gregory; Renz, Vanessa Deisi (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The question discussed in this paper is recovering Areas of Permanent Preservation (APP) stream Fatima degraded by human action, which is necessary for the recovery of biodiversity and by virtue of the Law. The study area is located in Fatima District, in the city of Frederico Westphalen, RS. Through visits to the local there was a series of impacts. Given this concern about the degraded areas, the present study aims to implement reforestation techniques for the place restoration and de population awareness to prevent future pollution.